Microstructure, Optical and Electrical Properties of Cu-Cu2O Core-Shell Nanostructures - Mondal, O. (Journal of Scientific Research, 2022)
Composites of nanometre-sized copper core–copper oxide (Cu-Cu2O) shell with different diameters were synthesized by a facile one step co-solvent technique. By the analysis of X-ray diffraction (XRD) and transmission electron microscope (TEM) data, the resultant particles were confirmed to be pure and nanocrystalline in nature. The perfect core-shell structure of nanocrystalline Cu-Cu2O was confirmed by using high resolution TEM. The presence of pure Cu and Cu2O was further confirmed from optical absorbance spectrum and Fourier transform infrared (FT-IR) spectroscopy. The tailoring of position of optical absorption peaks, originating from Cu or Cu2O nanoparticles, is possible by modulating the oil to water ratio, which controls the size of the composite particles and thickness of Cu2O. Drastic change of electrical resistivity with change in thickness of shell, has been observed. Variation of resistivity with temperature delineates a semiconducting nature with two distinct activation processes. Results demonstrate that the activation energies for the core-shell nanostructure composites were found to be smaller than the bulk Cu2O. Photoluminescence spectrum further confirms the semiconducting nature of the composite. In addition, the kinetic of core-shell morphology formation is also discussed briefly.